Adaptive Fixed‐Time Tracking Control for Switched Nonlinear Systems Subject to Multiple Input Constraints - Wang, Huanqing; Liu, Siwen; Zhang, Huaguang; Li, Tieshan (International journal of robust and nonlinear control, 2025)
In this paper, the issue of the adaptive fixed‐time control (FTC) is considered for switched nonlinear systems (SNSs) subject to multiple input constraints. The control input is simultaneously affected by the dead‐zone, saturation, and hysteresis, which is considered for the first time and the exact mathematical model is first given. Under the aid of backstepping technology and adaptive control, an adaptive FTC design strategy is produced. Introducing the common Lyapunov function (CLF), the designed control method makes certain that the state variables are bounded and the output variable tracks the reference signal in a known time where the initial variables of the systems have no influence on the setting time. Eventually, a simulation example shows the availability of the designed policy.